2018
DOI: 10.1108/ijphm-09-2016-0052
|View full text |Cite
|
Sign up to set email alerts
|

Development and testing of three unique scales measuring the brand image of nursing

Abstract: Purpose Nurses have been called to be leaders in the transformation of health care and to help improve health-care access for the nation’s most vulnerable populations. However, to lead health-care transformation, the profession of nurses must first see themselves as leaders. Unfortunately, nursing has been described as lacking cohesiveness and failing to communicate a consistent brand image. No empirically tested quantitative tools exist to measure the brand identity of nursing, making it difficult to assess w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…As discussed earlier in this paper, IOM recommendations have urged nurses to assume key roles ‘as team members and leaders for a reformed and better‐integrated, patient‐centered health care system’ (2010, preface, p. 12). Since nurses in this study indicated a desire for their brand image to be one of ‘leaders in education, research and practice' (Godsey et al, 2018), it could be assumed they are willing to assume such key roles. However, study findings suggest there is much work to be done if nurses are to be recognized and regarded as essential leaders throughout the health care system.…”
Section: Background: Review Of the Literaturementioning
confidence: 96%
See 4 more Smart Citations
“…As discussed earlier in this paper, IOM recommendations have urged nurses to assume key roles ‘as team members and leaders for a reformed and better‐integrated, patient‐centered health care system’ (2010, preface, p. 12). Since nurses in this study indicated a desire for their brand image to be one of ‘leaders in education, research and practice' (Godsey et al, 2018), it could be assumed they are willing to assume such key roles. However, study findings suggest there is much work to be done if nurses are to be recognized and regarded as essential leaders throughout the health care system.…”
Section: Background: Review Of the Literaturementioning
confidence: 96%
“…However, sparse studies exist, which clearly identify and quantitatively measure perceptions of the actual vs desired brand image and brand position for the nursing profession. In one such study, researchers conducted focus groups with nurses and then translated the resulting 42 themes into survey instruments measuring the current and most desired brand image of nursing (Godsey et al, 2018). Nursing's Current Brand Image Scale (NCBIS) and Nursing's Desired Brand Image Scale (NDBIS) were administered to a convenience sample of Bachelor of Science (BS) and Master of Science (MS) nursing alumni ( n = 286) using electronic surveys via SurveyMonkey.…”
Section: Background: Review Of the Literaturementioning
confidence: 99%
See 3 more Smart Citations